2015
DOI: 10.24198/agrikultura.v26i2.8469
|View full text |Cite
|
Sign up to set email alerts
|

Populasi Hama Wereng Batang Coklat (Nilaparvata Lugens Stal.) Dan Keragaman Serangga Predatornya Pada Padi Sawah Lahan Dataran Tinggi Di Desa Panyocokan, Kecamatan Ciwidey, Kabupaten Bandung

Abstract: Population of Brown Plant Hopper (Nilaparvata lugens Stal.) and the Diversity of Its Natural Enemyin Highland Paddy Rice Field in the Village of Panyocokan, Ciwidey District, Bandung RegencyBrown lanthopper/BPH (Nilaparvata lugens Stal.) is a main pest of rice in the field. This researchwas aimed to study the population of BPH and the diversity of its natural enemy in highland paddyrice field. The survey was conducted in three paddy plots (15 m x 20 m) located in the village ofPanyocokan, Ciwidey District, Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
6
0
3
Order By: Relevance
“…When the rice plant has entered the generative phase or matured phase, N. lugens usually moves to other fields to find young rice plants. Sianipar et al (2015) revealed that temperature, humidity, and rainfall did not have a major effect on the decline in the population of N. lugens, so that changes in the population of N. lugens were more influenced by the availability of host plants.…”
Section: Efficacy Of Mipc Insecticide On N Lugensmentioning
confidence: 96%
“…When the rice plant has entered the generative phase or matured phase, N. lugens usually moves to other fields to find young rice plants. Sianipar et al (2015) revealed that temperature, humidity, and rainfall did not have a major effect on the decline in the population of N. lugens, so that changes in the population of N. lugens were more influenced by the availability of host plants.…”
Section: Efficacy Of Mipc Insecticide On N Lugensmentioning
confidence: 96%
“…In this simulation, the brown planthopper is prey in the model, while menochilus sexmaculatus was the first predator and mirid ladybug as the second predator. To simulate the system (5), we use parameter values based on data from the agriculture, food, fisheries and marine services in the districts of Bantul, [6], [1], and [9], i.e. Based on data and [6], we obtained several parameters as follows: it will meet the conditions in the theorem.…”
Section: Simulationmentioning
confidence: 99%
“…To simulate the system (5), we use parameter values based on data from the agriculture, food, fisheries and marine services in the districts of Bantul, [6], [1], and [9], i.e. Based on data and [6], we obtained several parameters as follows: it will meet the conditions in the theorem. As a result, predators will become extinct while prey will survive and as shown in figure 1.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations